Utility of Glycated Albumin as a Biomarker for Glycemic Variability in Diabetes Mellitus - Mubashni, G.; Ignatius, Ignatius; Vibhuja, Vibhuja; Devadas, Bravian Samvict (Journal of Neonatal Surgery, 2025)
Introduction: Glycemic variability, characterized by short-term glucose fluctuations, is increasingly recognized as an independent risk factor for diabetes-related complications, including oxidative stress, inflammation, and vascular damage. Traditional markers like hemoglobin A1c (HbA1c) reflect average glucose levels over 2–3 months but fail to adequately capture glycemic variability. Glycated albumin (GA), a glycation product of serum albumin, offers an alternative, reflecting glycemic status over 2–3 weeks and remaining unaffected by factors such as red blood cell turnover. This study evaluates the utility of GA as a biomarker for glycemic variability compared to HbA1c. Materials and Methods: A cross-sectional study involving 120 participants with type 1 (n=55) or type 2 DM (n=65) was conducted. Glycemic variability metrics, including Mean Amplitude of Glycemic Excursions (MAGE), Coefficient of Variation (CV), and Time in Range (TIR), were derived from self-monitored blood glucose (SMBG) and continuous glucose monitoring (CGM). GA and HbA1c were measured using standardized enzymatic and HPLC assays, respectively. Correlation and ROC analyses assessed the relationship between GA, HbA1c, and glycemic variability. Results: GA showed stronger correlations with glycemic variability metrics than HbA1c (MAGE: r=0.72 vs. 0.45; CV: r=0.68 vs. 0.39; TIR: r=−0.63 vs. −0.34; all p<0.05). Subgroup analysis revealed GA's superior sensitivity in detecting glycemic excursions in participants with type 1 DM (MAGE: r=0.74) and type 2 DM with comorbidities such as anemia. ROC analysis demonstrated GA's higher predictive accuracy for glycemic variability (AUC=0.89) compared to HbA1c (AUC=0.76). Conclusion: GA provides a more sensitive measure of short-term glycemic variability than HbA1c, particularly in clinical scenarios where HbA1c may be unreliable, such as anemia or chronic kidney disease. By offering insights into glycemic excursions, GA has the potential to enhance personalized diabetes management, improve patient outcomes, and reduce complications. Future studies should explore its long-term impact on clinical care.